ANALISIS EFEKTIVITAS VISUALISASI LAPORAN KEUANGAN DENGAN INFOGRAFIS TERHADAP PENINGKATAN PEMAHAMAN PENGGUNA NON-PRAKTISI - Alfiya Ilfa; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2025)
This study aims to analyze the effectiveness of financial report visualizations using infographics in improving understanding among non-practitioner users. It compares the infographic format with conventional presentation formats to assess differences in perceived and actual understanding. The study also examines the moderating role of education level and explores the effects of accounting knowledge and financial statement familiarity.A quantitative method was applied through questionnaire distribution to 204 respondents across Central Java, including Semarang, Kudus, Demak, Kendal, and Jepara. The collected data were analyzed using the Wilcoxon Signed-Rank Test to examine differences in understanding, the Moderated Regression Analysis (MRA) to test the moderating effect of education level, and the Mann–Whitney U Test to assess the impact of knowledge and familiarity levels.The results show that infographic-based financial statements significantly enhance perceived and actual understanding compared to conventional formats. Education level is nearly significant as a moderator in the relationship between infographic presentation and actual understanding, while accounting knowledge and familiarity significantly influence actual understanding. These findings suggest that experiential factors play a greater role than formal education. The study highlights the importance of implementing visual tools such as infographics to promote financial literacy, particularly for non-practitioner users.